2002
DOI: 10.1097/00000539-200203000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Ropivacaine for Cesarean Delivery: A Comparison of Hyperbaric and Plain Solutions

Abstract: We compared hyperbaric and plain ropivacaine for combined spinal/epidural analgesia in the lateral position in patients undergoing elective cesarean delivery. Hyperbaric ropivacaine produced more rapid block with faster recovery and less requirement for epidural supplementation compared with plain ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
3
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 24 publications
10
54
3
8
Order By: Relevance
“…Many studies (Fettes et al, 2005;Whiteside et al, 2001;Kallio et al, 2004) showed that hyperbaric solutions of local anesthetics for spinal anesthesia produce a more rapid spread to a higher median level and less variation in maximum sensory and motor block and might enable a smaller dose to be used compared with plain solutions. Especially in pregnant women, the width of the hips is usually larger than the shoulders which result in a head-down tilt when lying in the lateral position (Khaw et al, 2002). By the way, compared with the results obtained by Khaw and colleagues and taking our results into account, the addition of glucose allows a reduction of nearly one third of the dose of ropivacaine required for the ED95 used in cesarean section.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Many studies (Fettes et al, 2005;Whiteside et al, 2001;Kallio et al, 2004) showed that hyperbaric solutions of local anesthetics for spinal anesthesia produce a more rapid spread to a higher median level and less variation in maximum sensory and motor block and might enable a smaller dose to be used compared with plain solutions. Especially in pregnant women, the width of the hips is usually larger than the shoulders which result in a head-down tilt when lying in the lateral position (Khaw et al, 2002). By the way, compared with the results obtained by Khaw and colleagues and taking our results into account, the addition of glucose allows a reduction of nearly one third of the dose of ropivacaine required for the ED95 used in cesarean section.…”
Section: Discussionsupporting
confidence: 62%
“…However, ropivacaine has a lower central nervous system and cardiotoxic potential than bupivacaine. Many investigators reported that ropivacaine can be used safely for spinal anesthesia in obstetric patients (Khaw et al, 2002;Gautier et al, 2003). Dose requirements of spinal plain ropivacaine for cesarean section have variable range from 8 to 22.5 mg, and a previous dose-response study with plain ropivacaine for cesarean section had estimated the 95% effective dose (ED95) to be 26.8 mg (Khaw et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Khaw KS et al, [2] compared the cephalic spread and reliability between hyperbaric and isobaric ropivacaine. Hyperbaric solution tends to spread by gravity while in isobaric (plain) solution no effect of gravity assisted spread is seen and tends to concentration at segment near the site of injection.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies like Khaw KS et al, [2], Gupta R et al, [8], Whiteside JB et al, [9] have reported faster rate of onset and offset of sensory and motor blockade in hyperbaric solution than plain solution, but in study done by Kallio H et al, [6] they found no difference between hyperbaric and plain ropivacaine (15 mgs) in median onset of analgesia to T10, and in time taken to reach the highest level of sensory block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation